Academic Supervision Management for Enhancing Teacher Competence - Basin Basin; Waska Warta (CV. Media Digital Publikasi Indonesia, 2026)
Enhancing teacher competence is a crucial factor for achieving effective learning quality in elementary schools. However, the implementation of academic supervision by principals as a primary coaching instrument often faces various challenges, ranging from time constraints to less impactful methods. This gap between the ideal role of supervision and the reality in the field motivates this research. Therefore, this study aims to describe and analyze in-depth the management of academic supervision at SDN 274 Cempaka Arum and SDN 052 Cisaranten Wetan in an effort to improve teacher competence. This research employs a qualitative approach with a descriptive-analytical method and applies George R. Terry's management framework (POAC) as its theoretical basis. Data were collected through interviews, observations, and documentation studies. The research findings reveal two different yet equally effective management models. (1) SDN 274 Cempaka Arum implements a formal-structured model, characterized by systematic planning, team-based organization, implementation through clinical coaching, and documented evaluation. (2) Conversely, SDN 052 Cisaranten Wetan utilizes an informal-personal model, featuring flexible planning, principal-centered organization, a humanistic implementation, and direct, personal evaluation. The study also identifies the main constraint at SDN 274 as time limitation, which was addressed through delegation, while at SDN 052, it was potential subjectivity, which was overcome by prioritizing dialogue and trust. The conclusion of this study confirms that the management of academic supervision, planned and executed adaptively through either a formal-structured or an informal-personal model, is an essential function proven to enhance teacher competence, thereby directly impacting the improvement of learning quality in elementary schools.